2021
DOI: 10.3390/su13179597
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Research Works on Supervised Learning Algorithms for SCADA Intrusion Detection and Classification

Abstract: Supervisory Control and Data Acquisition (SCADA) systems play a significant role in providing remote access, monitoring and control of critical infrastructures (CIs) which includes electrical power systems, water distribution systems, nuclear power plants, etc. The growing interconnectivity, standardization of communication protocols and remote accessibility of modern SCADA systems have contributed massively to the exposure of SCADA systems and CIs to various forms of security challenges. Any form of intrusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 113 publications
0
14
0
Order By: Relevance
“…The researchers in [8] proposed an efficient framework that learns minimal temporal preferential attack targeting the LSTM model with electronic medical record inputs, they also proposed an efficient and effective framework that identifies sensitive locations in medical records using adversarial attacks on deep predictive models. The results showed weakness in the deep models, as it was more than half of patients can be successfully attacked by changing only 3% of the recording sites with maximum perturbation less than 0.15 and mean perturbation less than 0.02.…”
Section: Related Workmentioning
confidence: 99%
“…The researchers in [8] proposed an efficient framework that learns minimal temporal preferential attack targeting the LSTM model with electronic medical record inputs, they also proposed an efficient and effective framework that identifies sensitive locations in medical records using adversarial attacks on deep predictive models. The results showed weakness in the deep models, as it was more than half of patients can be successfully attacked by changing only 3% of the recording sites with maximum perturbation less than 0.15 and mean perturbation less than 0.02.…”
Section: Related Workmentioning
confidence: 99%
“…Theoretical investigation revealed that with random parameters, ELM is more likely to obtain a global optimal solution than traditional networks with all the parameters to be trained [90]. ELM is quite popular nowadays because of its variety of applications such as robotics [91], IoT-based models [92][93][94], control systems [93], etc., as well as its high accuracy, cross-domain adaptation, and low time consumption (training time mostly).…”
Section: Extreme Learning Machinementioning
confidence: 99%
“…The CICIDS-2017 dataset is a recently generated open-source dataset provided by the Canadian Institute of Cybersecurity for intrusion detection. The CICIDS-2017 dataset has the attributes of practical real-life network traffic, and its labeling is based on the timestamp, source and destination IPs, source and destination ports, protocols, and attacks [50]. This dataset was captured over a duration of 5 days with 2,830,743 records, 80 network traffic features, and 15 attack types.…”
Section: Used Datasetsmentioning
confidence: 99%